2020
DOI: 10.1158/1940-6207.capr-20-0095
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Modulation Study of Celecoxib for Chemoprevention in Women at Increased Risk for Breast Cancer: A Phase II Pilot Study

Abstract: In preclinical studies, celecoxib has been associated with reduced risk of breast cancer. In this study, the aim was to assess the biomodulatory effect of celecoxib on blood and benign breast tissue biomarkers in women at increased risk for breast cancer. Women at increased risk for breast cancer [5-year Gail risk score of >1.67%, history of atypical hyperplasia, lobular carcinoma in situ, or previous estrogen receptor (ER)-negative breast cancer] were treated with celecoxib at 400 mg orally twice daily for 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…We propose that clinical prevention trials evaluating the efficacy of NSAIDs for breast cancer prevention among women with BBD that incorporate correlative studies to examine interactions between inflammation and estrogen pathways in breast tissues are warranted. A recently completed phase II trial of celecoxib 400 mg twice daily for 6 months, demonstrated good tolerance with favorable modulation of selected biomarkers (42).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that clinical prevention trials evaluating the efficacy of NSAIDs for breast cancer prevention among women with BBD that incorporate correlative studies to examine interactions between inflammation and estrogen pathways in breast tissues are warranted. A recently completed phase II trial of celecoxib 400 mg twice daily for 6 months, demonstrated good tolerance with favorable modulation of selected biomarkers (42).…”
Section: Discussionmentioning
confidence: 99%
“…In other phase II trials however, celecoxib treatment (NCT00300729) or adding celecoxib to concurrent chemoradiation (NCT01503385) did not improve survival of NSCLC patients [294,295]. In a phase II trial, celecoxib induced favorable changes in serum biomarkers and cytology in women with increased risk for breast cancer [296]. Notably, the improvement of prognosis by celecoxib-based combination treatment is more prominent in patients with tumors expressing higher levels of COX-2 [297].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 96%
“…Initial efforts to examine this question by evaluating the effect of PGE 2 inhibition using celecoxib, a selective COX2 inhibitor, on tissue biomarkers of proliferation (Ki-67) were terminated due to toxicity concerns. Revisiting this, a recently completed study of women at increased risk for breast cancer treated with 400 mg celecoxib twice daily for 6 months using random periareolar fine-needle aspiration sampling of the breast support favorable changes in cytology but no change in tissue Ki-67 or estrogen receptor (ER) expression (19). Observational studies of NSAID use for effects on BD using mammographic measurements have also been largely null though for women followed prospectively, those who continued NSAID use were more likely to remain low density than those who discontinued use (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%